Mezinárodní srovnání lékové compliance a faktorů ovlivnujících non-complianci u seniorů s polyfarmakoterapií - Topinková, E; Fialová, D; Carpenter, G I; Bernabei, R (Casopis lekaru ceskych, 2006)
BACKGROUND: Population of seniors in the Czech Republic consumes more than 35 % of all prescribed medications. Currently, Czech seniors take on the average 4-5 prescribed drugs. However, our knowledge about factors influencing drug compliance is scarce particularly in seniors with polypharmacotherapy. Non-compliance can contribute to treatment failure and increases the risk of adverse drug reactions. The aim of the study is to compare drug compliance in the elderly in 11 European countries and to assess the impact of demographic and drug-related factors on non-compliance to medication. METHODS AND RESULTS: Cross-sectional comparative study in 3881 elderly subjects living in the community receiving home-care services in 11 European countries participating in ADHOC (Aged in Home Care) study. In the sample of Czech subjects we performed in-depth analysis of causes and factors associated with non-compliance in patients with polypharmacotherapy. 12.5% (n=456) of European seniors were non-compliant with prescribed medication with significantly higher prevalence of non-compliance in the CR (33.5 %) and Germany (17.0 %). In the Czech sample following non-compliance risk factors have been identified: taking > or = 7 drugs per os (OR= 2.2), 10 single applications/day (OR= 2.5), more than twice daily dosing (OR= 2.4), problems with drug preparation (OR= 4.6), polypharmacotherapy 5 years and longer (OR= 5.5) and drug preparation without supervision or help (OR= 2.8). The highest prevalence of non-compliance was found for antidepressants (80 %), antiasthmatics (68 %), fibrates (60 %), nonsteroidal antiinflammatory drugs, vasodilatators, anticoagulants/antiplatelet drugs and nootropics (50 %). Among the most common causes, patients reported forgetting to take the drug (74.3 % patients), mistrust in drug effect (10.6%) and fear of taking "too many drugs" (8.6 %). CONCLUSIONS: Non-compliance to prescribed drug regimen is a prevalent problem in one third of the Czech seniors and was found to be the highest among 11 European countries. Doctors prescribing to older people have to monitor purposefully compliance and strenghten co-operation and motivation of the patient to adhere with prescribed drug regimen. Particularly in seniors with polypharmacotherapy it seems necessary to simplify drug regimen as much as possible. In elderly patients with physical disability, cognitive impairment or depression supervision and/or help of another person with drug preparation and application may improve drug compliance.
Keywords: Aged; Patient Compliance; polypharmacy; Humans; Česká republika; senioři; adherence pacienta; lidé; Europe; Polypharmacy; Evropa; Czech Republic